Qualitative research on the lived experience of psychosis: A methodological review - Γεωργάκα, Ευγενία (Psychology: the Journal of the Hellenic Psychological Society, 2020)
This paper provides a methodological review of qualitative studies on the lived experience of psychosis. It aims to present the main research trends on psychotic experience and to assess their usefulness and appropriateness for examining the role of social factors in the emergence, experience and management of psychosis. The following trends are presented: (a) the phenomenological approach, which aims to identify the essence of psychotic experience, (b) the narrative and dialogical approaches, which focus on the constitution of the self in psychosis through the examination of self-narratives, (c) the social constructionist approach, which, through analysing the discourse of persons in distress, examines the construction of mental distress, and finally (d) empirical studies employing thematic type qualitative analysis on interviews with persons in distress in order to highlight their experiences and views regarding various aspects of their life with psychosis. For each of the approaches, the paper addresses: (a) its epistemological paradigm, (b) the view of psychosis and mental distress adopted, (c) the research methodology used regarding data collection and analysis, (d) the main findings and conclusions, and (e) the role attributed to social factors and processes.